2017
DOI: 10.1016/j.ijporl.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Acute mastoiditis in children: Middle ear cultures may help in reducing use of broad spectrum antibiotics

Abstract: a b s t r a c tBackground: Acute mastoiditis (AM) is a suppurative infection of the mastoid air cells, representing the most frequent complication of acute otitis media. AM remains an important entity in children due to its potential complications and sequelae. We aim to describe the cases of AM admitted at our department, identify risk factors potentially associated with complications and analyse the changes in clinical approach of AM over time. Methods: Case review of clinical files of children admitted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
(26 reference statements)
0
7
1
Order By: Relevance
“…35 Most clinicians would however agree that imaging is indicated when the clinical course is complicated or prolonged, or when clinical signs suggest complications. 33 Our meta-analysis showed that age group was an influential factor in IMO prevalence. Placanica et al 24 and Lafferty et al 23 demonstrated an inverse linear correlation between age and IMO.…”
Section: Comparison With Existing Literaturementioning
confidence: 74%
See 3 more Smart Citations
“…35 Most clinicians would however agree that imaging is indicated when the clinical course is complicated or prolonged, or when clinical signs suggest complications. 33 Our meta-analysis showed that age group was an influential factor in IMO prevalence. Placanica et al 24 and Lafferty et al 23 demonstrated an inverse linear correlation between age and IMO.…”
Section: Comparison With Existing Literaturementioning
confidence: 74%
“…Some authors advocate an early CT scan in all patients to classify true mastoiditis into incipient or coalescent subtypes, 34 while others argue imaging is not mandatory 35 . Most clinicians would however agree that imaging is indicated when the clinical course is complicated or prolonged, or when clinical signs suggest complications 33 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[42][43][44][45][46] A shift in etiology of bacterial AOM in the PCV and HiB vaccination era may also explain why an ear infection, though very rarely, is still complicated by mastoiditis, and extremely rarely by meningitis and other forms of intracranial extension of infection. [47][48][49] A cross-sectional analysis of the US Kids National Inpatient Database had demonstrated a reduction in the incidence of acute mastoiditis from 8 per 10 000 hospital discharges in 1997 to 3.4 per 10 000 hospital discharges in 2009 in patients aged between 1 and 4 years. 50 Even in the Pittsburg cohort, among children treated with watchful waiting, only 1 (0.7%) developed mastoiditis.…”
Section: Discussionmentioning
confidence: 99%